2007
DOI: 10.1111/j.1567-1364.2007.00246.x
|View full text |Cite
|
Sign up to set email alerts
|

Multigene phylogenetic analysis of the Lipomycetaceae and the proposed transfer ofZygozymaspecies toLipomycesandBabjevia anomalatoDipodascopsis

Abstract: Phylogenetic relationships among species assigned to genera of the family Lipomycetaceae were determined from analysis of the nearly entire large, subunit rRNA gene, the small subunit rRNA gene, mitochondrial small subunit rRNA gene and the translation elongation factor-1alpha gene. Monophyly of the Lipomycetaceae was strongly supported, and currently described species appear genetically unique. The multigene analysis provided no support for maintaining the genera Kawasakia, Smithiozyma, Waltomyces or Zygozyma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
23
0
1

Year Published

2008
2008
2018
2018

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 34 publications
(25 citation statements)
references
References 24 publications
1
23
0
1
Order By: Relevance
“…2 and Table S1 in supplementary material). Recent phylogenetic analysis showed that the species delimitation of L. mesembrius and L. doorenjongii was unresolved by the D1/D2 LSU rRNA gene (Kurtzman et al 2007). In this study, we classified the L. mesembrius-L. doorenjongii clade (Fig.…”
Section: Relationships Between Phylogeny and Ability Of Lipid Productionmentioning
confidence: 94%
See 1 more Smart Citation
“…2 and Table S1 in supplementary material). Recent phylogenetic analysis showed that the species delimitation of L. mesembrius and L. doorenjongii was unresolved by the D1/D2 LSU rRNA gene (Kurtzman et al 2007). In this study, we classified the L. mesembrius-L. doorenjongii clade (Fig.…”
Section: Relationships Between Phylogeny and Ability Of Lipid Productionmentioning
confidence: 94%
“…Phylogenetic analysis of partial 5.8S rRNA and internal transcribed spacer (ITS) 2 sequences showed that L. starkeyi s.s. and its associated clusters b and c, and L. mesembrius formed a monophyletic group with L. tetrasporus (Gouliamova et al 1998). Kurtzman et al (2007) performed phylogenetic analysis of the Lipomycetaceae based on each four genes (D1/D2 domain of LSU rRNA gene, SSU rRNA gene, mitochondrial SSU rRNA gene, and the EF-1a gene), and now L. mesembrius, L. doorenjongii and L. kockii are accepted in YEAST, 5th edition (Smith and Kurtzman 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Kurtzman et al (2007) constructed a phylogenetic tree based on the concatenated sequences from the nearly entire 18S rRNA, 26S rRNA, mitochondrial small subunit rRNA and the EF-1α genes and showed that the family Lipomycetaceae, including the genera Lipomyces, Dipodascopsis, Zygozyma and Babjevia, has a monophyletic lineage since the bootstrap value of 100% was calculated between the cluster including Babjevia anomala and (Smith 1998a, b). According to Nakase and Komagata (1970), such an emended genus that is genetically diverse has a heterogeneous nature taxonomically.…”
Section: Resultsmentioning
confidence: 99%
“…The following references will provide an introduction to the rapid changes occurring in ascomycete yeast classification: Kurtzman and Robnett [18,88], Kurtzman and Suzuki [89] and Kurtzman et al [31,49,90]. The paper of Rokas et al [91] should also be consulted because it addresses the issue of minimum number of gene sequences needed for an accurate species phylogeny within genera.…”
Section: Discussionmentioning
confidence: 99%